Pertumbuhan dan Kelangsungan Hidup Ikan Putak (Notopterus notopterus, Pallas 1769) yang Dipelihara dalam Waring di Sungai Kelekar - Muslim, Muslim; Syaifudin, Mochamad; Taqwa, Ferdinand Hukama; Hamdani, Hijral (Jurnal Sumberdaya Akuatik Indopasifik, 2024)
The bronze featherback (N. notopterus, Pallas 1769) is one of Indonesia's native fish species. This species has been protected by the Indonesian government. Domestication of this species is very important for its sustainability. The aim of this study was to evaluate the impact of different stocking densities on growth, survival, and feed efficiency. N. notopterus is reared in net cages. The research treatments were stocking densities of 1, 3, and 5 fish.m-2 with three replications. The initial body weights of N. notopterus were 55.40 ± 3.40; 55.41 ± 2.90; and 56.07 ± 1.06 g, respectively. The growth trial lasted for 60 days, from May to July 2023. The individual weights of fish in each net cage were recorded monthly. The final body weights of the fish stocked at densities of 1, 3, and 5 fish.m-2 reached 66.87±2.17, 67.63±3.06, and 64.93±0.72 g, respectively. The specific growth rate values were 0.45, 0.48, and 0.34% day-1 at temperatures ranging between 25.1 and 30.3°C. The feed efficiency values were 8.36, 9.04, and 6.30%, and the survival rates were calculated at 100, 100, and 93.3%, respectively. The results revealed that stocking density had a significant effect on the growth and feed efficiency of N. notopterus. The results of this study showed that the stocking density of 3 fish.m-2 was the best treatment.